'DAMIT DIE SEELE DIESER FRAU NICHT ÜBERSEHEN WERDE BEIM SAMMELN DES LEBENS': RE‐ENACTMENT AND THE SEARCH FOR KNOWLEDGE IN VIOLA ROGGENKAMP'S DIE FRAU IM TURM (2009). (October 2014) - Brook, Madeleine; Woodford, Charlotte; Colvin, Sarah
ABSTRACT Telling history is, famously, a process of 're‐enacting' past experience through 're‐thinking' it – and in 're‐thinking' that past experience, the historian also understands something about himself (Collingwood). These ideas are at the root of a great deal of modern pedagogical thought with reference to teaching history. The character of Masia Bleiberg in Viola Roggenkamp's novel, Die Frau im Turm (2009), however, takes a more subjective and emotionally driven approach to employing re‐enactment as a way to find out about herself. As the thirty‐something daughter of a Jewish Holocaust survivor now living in the GDR and a West German mother, she tries to establish her identity through exploring a number of 're‐enactment' strategies, many of which prove unsatisfactory. Masia's search for knowledge proves to be highly gendered: while female characters produce knowledge and the record of it, it is the male characters who act as the gatekeepers to the (self‐)knowledge Masia seeks.